Poly-Orogenic Melting of Metasedimentary Crust From a Granite Geochemistry and Inherited Zircon Perspective (Southern Calabria-Peloritani Orogen, Italy) - Fiannacca, Patrizia; Williams, Ian S.; Cirrincione, Rosolino; Pezzino, Antonino (Frontiers in Earth Science, 2019)
Inherited zircon ages and geochemical features of late Cadomian and late Variscan granitoids from the north-eastern Peloritani Mountains (NE Sicily) and the western Aspromonte Massif (SW Calabria) shed new light on the sources and processes involved in poly-orogenic granitoid magmatism. The two groups of strongly peraluminous granitoids have similarities in trace element abundance patterns and Sr and Nd isotopic compositions consistent with both being derived from crustal sources, possibly with a minor contribution from mantle-related components. Comparison of the granite compositions with those of experimental melts derived from various metaigneous and metasedimentary sources indicates that both groups of granitoids originated exclusively from different degrees of melting of similar greywacke-dominated turbidite. Abundant inherited zircon cores from representative samples of metamorphosed late Cadomian (545 ± 5 Ma) granite and late Variscan (300 ± 4 Ma) leucogranodiorite have the same range of U-Pb ages, from Early Paleoproterozoic to latest Neoproterozoic, with main age clusters at 0.55 and 0.63 Ga, and minor age clusters at 0.95 and 2.5 Ga. The pattern of detrital zircon ages from a paragneiss, host rock to the late Cadomian granite, is the same, indicating, in conjunction with the geochemistry, that both granites originated by partial melting of deeper crustal equivalents of those paragneisses. The same crustal sequence melted during successive orogenies under different thermal regimes and in different post-collisional tectonic settings, giving rise to granitoid associations with different ages and geochemical features largely reflecting the melting conditions. On the other hand, the zircon inheritance patterns and specific chemical features of S-type granitoids reflect the nature of their crustal magma sources, independently from the effects of the thermal regime or tectonic setting at the time of magmatism.